The Influence of E-Kinerja Implementation and Incentives (Reward) on the Performance of Village Officials - Negara, I Made Dwija Oka (Journal of Economics and Public Health, 2025)
This study aims to empirically analyze and test the simultaneous and partial impact of E-Kinerja (electronic performance system) implementation and the provision of Reward on the Performance of Village Officials within the Jembrana Regency Government. The background of this study is based on the challenges faced by the Jembrana Regency Government in measuring and evaluating the performance of its numerous village officials, which led to the adoption of the E-Kinerja system as a more objective and accurate assessment solution. The research method used is hypothesis testing with Multiple Linear Regression Analysis. Primary data was collected from 67 Village Officials via questionnaires. The results indicate that E-Kinerja and Reward simultaneously have a significant and positive influence on Village Officials Performance, with a Correlation Coefficient (R) of 0.731, classified as a strong relationship. The Coefficient of Determination (R2) of 0.535 suggests that 53.5% of the performance variation can be explained by these two independent variables. Partially, both E-Kinerja (β1 = 0.288) and Reward (β2 = 0.490) were found to have a positive and significant effect. In conclusion, the implementation of E-Kinerja and the provision of Reward are crucial factors that significantly contribute to improving the quality of Village Officials' performance in Jembrana Regency.